Achievement Motivation in Late Adolescence: A Systematic Review of Educational and Social Determinants - Saniya Nurmukhambetova (Theoretical Hypotheses and Empirical Results, 2025)
This review synthesizes contemporary research (2010–2023) on the factors influencing the development of achievement motivation in adolescents aged 15–18. The focus is on the interplay between individual psychological characteristics, the educational environment, and the broader social context. The methodology involved a systematic search and analysis of articles in the Scopus, Web of Science, and PsycINFO databases using key term combinations. The review's findings are structured around three primary determinants: 1) the role of school and pedagogical practices, 2) the influence of family and peers, and 3) cognitive-personality factors (growth mindset, self-regulation). The analysis reveals that a supportive educational environment combining high expectations with autonomy is a key condition. Parental influence transforms from direct control to a consultative role, while peer influence becomes ambivalent, serving as both a source of support and social comparison. Special attention is paid to gender differences and the impact of the digital environment. The review identifies methodological gaps, including a lack of longitudinal and cross-cultural studies, and suggests directions for future research aimed at creating ecosystemic models of motivation support.